2015
DOI: 10.1101/030189
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recovery of dynamics and function in spiking neural networks by closed-loop control

Abstract: There is a growing interest in developing novel brain stimulation methods to control disease--related aberrant neural activity and to address basic neuroscience questions. Conventional methods for manipulating brain activity rely on open-loop approaches that usually lead to excessive stimulation and, crucially, do not restore the original computations performed by the network. Thus, they are often accompanied by undesired side-effects. Here, we introduce delayed feedback control (DFC), a conceptually simple bu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Similarly, closed-loop ES systems are being developed for Parkinson's disease [Beuter et al, 2014] and stroke patients [Fujiwara et al, 2009], and have demonstrated to be more effective deep-brain stimulation parameters when combined with hippocampal theta oscillations as a feedback input [Wu et al, 2015]. Furthermore, the development of closed-loop system algorithms for improved neuromodulation has gained recent attention [Liu et al, 2011;Vlachos et al, 2016].…”
Section: Closed-loop Neural Prostheticsmentioning
confidence: 99%
“…Similarly, closed-loop ES systems are being developed for Parkinson's disease [Beuter et al, 2014] and stroke patients [Fujiwara et al, 2009], and have demonstrated to be more effective deep-brain stimulation parameters when combined with hippocampal theta oscillations as a feedback input [Wu et al, 2015]. Furthermore, the development of closed-loop system algorithms for improved neuromodulation has gained recent attention [Liu et al, 2011;Vlachos et al, 2016].…”
Section: Closed-loop Neural Prostheticsmentioning
confidence: 99%
“…This method has interesting properties that make it attractive for neuromodulation applications: it does not require prior knowledge about the controlled system, the actuation signal vanishes as the system approaches the desired trajectory (be it a stable orbit or its suppression), it is simple and easy to implement both in software and hardware and the eventual technical latencies can be compensated by adjusting the delay accordingly. DFC has been extensively applied in the context of neuroscience, with studies focusing on specific disorders such as Parkinson's Disease [15][16][17][18][19][20] and epilepsy 21 . However, there is still controversy in the literature regarding its efficacy and whether it may instead promote synchrony depending on the baseline levels of synchrony of the modelled network 22 .…”
Section: Introductionmentioning
confidence: 99%